The relational economy: geographies of knowing and learning - Bathelt, Harald; Glückler, Johannes (Oxford University Press, 2011)
"How are firms, networks of firms, and production systems organized and how does this organization vary from place to place? What are the new geographies emerging from the need to create, access, and share knowledge, and sustain competitiveness? In what ways are local clusters and global exchange relations intertwined and co-constituted? What are the impacts of global changes in technology, demand, and competition on the organization of production, and how do these effects vary between communities, regions, and nations? This book synthesizes theories from across the social sciences with empirical research and case studies in order to answer these questions and to demonstrate how people and firms organize economic action and interaction across local, national, and global flows of knowledge and innovation
Includes bibliographical references
Keywords: Wirtschaftsgeografie; Anthropogeografie